394 Fungal keratitis in auxiliary garbage collector as an occupational disease. case report. (24th April 2018) - Sanchez, BS; Contreras, Y; Avelar, S; Hurtado, P
Abstract : Introduction: Infectious keratitis is a serious ocular pathology with potentially catastrophic visual results, being this one of the most prevalent causes of irreversible blindness worldwide, according to the WHO, with a prevalence ranging from 6% to 60%, predominantly in developing countries. Methods: 45 years old man worker, with history of myopia with contact lens wear for 3 year, urban waste collector since 3 years and 9 months ago, without personal protection equipment, while, working had a right eye exposure from a garbage bag that was being compressed in a collecting truck, rubbing his eye immediately and removing contact lenses 5 hours later. One day later, he presented decreased visual acuity, hyperemic conjunctiva and leukoma, appearing to the ophthalmologist who indicated moxifloxacin ophthalmic, presenting partial recovery of visual acuity. 15 days later he continued with leukoma, which yielded to treatment with fluconazole, but the evolution continued with sudden decrease in vision 20/400, establishing diagnosis of 5 × 4 mm corneal ulcer, receiving treatment with a patch of cyanoacrylate and a bandage lens on 3 occasions without improvement, requiring corneal transplantation performed 8 months later. Results: Direct fundoscopy, Goldmann lens: papilla with excavation of 0.4 × 0.4 mm, central emergency vessels, slimmed vascular pattern, cornea with central opacity at stromal oedema expenses and corneal centre ulcer of 5 × 4 mm. Discussion: During garbage collection workers are exposed to biological agents such as Aspergillus, Fusarium and Candida from organic materials; That without the use of appropriate personal protective equipment and combined with the use of contact lenses increases the risk of developing ocular pathologies such as fungal keratitis. Through symptomatology, physical exploration, and evolution of the pathology, the causal relationship was corroborated, cause-effect, work-injury, being determined as if occupational disease.